Responses of antioxidant defense capacity and photosynthesis of bean (Phaseolus vulgaris L.) plants to copper and manganese toxicity under different light intensities - Hajiboland, Roghieh; Hasani, Behrokh D. (Acta Biologica Szegediensis, 2007)
Effects of toxic concentrations of Cu and Mn were studied in bean (Phaseolus vulgaris) plants under different light intensities. Exposure of plants to 100 pM Cu, inhibited their growth up to 79%, while similar concentrations of Mn caused only a slight (21%) reduction of plants dry weight. Net assimilation rate (A) was inhibited with similar extent by both heavy metals and FJF0 ratio decreased particularly by Mn treatment. With the exception of ascorbate peroxidase in Cu treated plants, activity of catalase, superoxide dismutase and glutathione reductase were stimulated by both heavy metals with similar extent. Change in guaiacol peroxidase activity was correlated with growth response, increased by Cu but was not affected by Mn toxicity. Similar to peroxidase activity, accumulation of proline monitored the stress conditions but did not cause more protection against Cu toxicity. On the other hand, concentration of H202 and malondialdehyde indicated a higher oxidative stress simultaneous with higher growth in the Mn than Cu treated plants. Results imply that, growth response to Cu and Mn could be reflected neither by the chlorophyll fluorescence nor the net assimilation rate. Additionally, antioxidant defense capacity did not involve in different response to Cu and Mn in bean plants.